THE ROLE OF OCCUPATIONAL AND DEMOGRAPHIC FACTORS IN RELATION TO WORK ENGAGEMENT IN POLISH SAMPLE OF EMPLOYEES – INITIAL STUDY - Jaworek, Magdalena (Journal of Positive Management, 2018)
Purpose: The aim of the present study is to analyze the differences in work engagement in terms of occupational groups (teachers, nurses, physicians, policemen, telesales operators, blue collar workers, employing in accounting/finance, sales representatives, welfare services/rehabilitation, office workers in public sector, and bank and IT employees), job position (managerial and non-managerial), age, and gender in Polish sample of employees. Methodology: A cross-sectional questionnaire survey was conducted among 3186 employees representing different occupational groups. The measure was the Utrecht Work Engagement Scale (UWES-9) by Schaufeli and Bakker (2003). To examine differences in work engagement in terms of occupational group and age, one-way ANOVA and post-hoc tests (Tukey’s HSD) were conducted. Differences in work engagement concerning job position and gender were performed using independent samples t tests. Findings: The findings indicated that employees differ in work engagement depending on studied factors. In terms of occupational group, the most engaged are sales representatives, welfare services/rehabilitation, and teachers, and least engaged - telesales operators and blue collar workers. Older employees (+50) appeared to be more engaged than youngers, as well managers in comparison to non-managers. While women reported higher level of absorption and dedication than men, but no gender differences were observed in regard to vigor. Implications: Results show that occupational factors, as profession and job position, as well demographic ones should not be ignored in relation to work engagement. Managers, in order to increase engagement among their subordinates should pay special attention to some groups of employees in terms of age, gender, and the occupation. Originality/value: The current study extends previous research by examining occupational and demographic differences in the level of work engagement. To the best of author’s knowledge this is the first examination of this type conducted in such large sample among Polish employees.